Geeks, gamers, and girls: revealing diverse digital identities with membership categorisation analysis. Issue 6 (2nd November 2019) - McLay, Katherine F.
ABSTRACT: The 'digital imperative' of contemporary education practice is without contention; however, much learning technology research has focused on pragmatic issues such as learning design, often founded on uncritically accepted claims about 'digital natives'. This focus has come at the expense of learning theory. Alongside the scholarly voices calling for education research to redress this imbalance, there is increasing interest in the role played by technology not only in epistemological learning, but also in the ways technology is an identity issue. This paper explores how membership categorisation analysis opens up ways of understanding the role of technology for contemporary learner identities. Examination of student talk makes visible the diverse ways of being an iPad-using student, challenges widely-accepted constructions of contemporary learners as generationally uniform, and contributes to a more holistic conception of learning that accounts for the role played by technology in learning identity.